Pattern of Tuberculosis, Trend and Outcome of Patients Registered at DOTS Centre of a Tertiary Care Hospital - Pant, Pankaj; Joshi, Aishana; Adhikari, Yagya Raj; Rijal, Yasoda; Ghimire, Sharmila; Gautam, Ashmita; Shah, Sangam; Bam, Niraj; Das, Santa Kumar (Journal of Nepal Health Research Council, 2022)
Background: Tuberculosis is a common respiratory disease imposing significant health burden. Directly observed treatment short course strategy ensures patient compliance in tuberculosis treatment. The aim of this study was to assess pattern of tuberculosis, trend and outcome of patients registered at Directly observed treatment short course centre of Tribhuvan University Teaching Hospital. Methods: A retrospective observational study was conducted at Tribhuvan University Teaching Hospital. Tuberculosis patients of all age groups registered from July 2017 to June 2020 at Tribhuvan University Teaching Hospital Directly observed treatment short course centre were included. Data entry and analysis was done in SPSS version 20.0. Descriptive statistics was performed and results were interpreted in mean, frequency and percentage. Results: A total of 2790 tuberculosis patients were included for final analysis. There were 1736 (62.2%) males. Mean age of patients was 37.94±20.28 years. Pulmonary tuberculosis was the most common type of tuberculosis seen in 948 (34%) patients. Fifty percent of total tuberculosis cases were confined to thorax. Tubercular pleural effusion and pleurisy (14.6%), central nervous system (13.2%), bone and joint (12.2%) were common forms of extrapulmonary tuberculosis. The mean incident tuberculosis cases registered annually was 697.5±95.63. Nearly half (49.1%) of the patients completed tuberculosis treatment regimen while 43.3% were referred to other Directly observed treatment short course centre as per their convenience. Conclusions: This study reflects the trend and pattern of tuberculosis epidemiology at tertiary care hospital of Nepal. There is a huge burden of both pulmonary and extrapulmonary tuberculosis at Tribhuvan University Teaching Hospital with slight annual variation in incident tuberculosis cases. Despite implementation of Directly observed treatment short course, the problem of non-compliance persists among the tuberculosis patients. Keywords: DOTS; tuberculosis; tertiary centre.